A simplified heat transfer model of a closed refrigerated display cabinet. (1st June 2020) - Chaomuang, Nattawut; Laguerre, Onrawee; Flick, Denis
Highlights: A simplified heat transfer model base on the zonal approach was developed for a closed display cabinet. Air and load temperatures at different positions were measured in the display cabinet. The model allows good prediction of average air and load temperatures. The effect of external air infiltration through door gaps was addressed. Abstract: Installation of doors on open refrigerated display cabinets is one of the simple and effective methods to improve the cabinet performance because it can reduce the warm and humid air infiltration into the cabinets. However, the presence of doors can change airflow pattern, which in turn influences the heat transfer and product temperatures. It is, thus, necessary to understand these thermal phenomena. This study proposes a simplified heat transfer model developed based on a zonal approach to describe the evolution of air and product temperatures at different zones in the closed refrigerated display cabinet. For model validation, the predicted values were compared with measured air and load temperatures for three external air temperatures. Good agreement was found between the predicted and measured temperatures with the maximum difference of less than 0.5 °C for every studied position and the overall mean absolute error of 0.2 °C. The model was then used to predict the effect of the air infiltration through the door gaps on the performance of the closed display cabinet in both thermal and energy aspects. This developed model will be further used in the modeling of the cold chain, where several types of refrigeration equipment are used to keep products under low-temperature conditions from production to consumption. Through integration of quality and microbiological predictive models, this approach can be used as a numerical tool for an evaluation tool for consumer risk.